Enhanced removal of chiral emerging contaminants by an electroactive biofilter - Álvaro Pun; Jesús Valimaña-Traverso; María Ángeles García; María Luisa Marina; Abraham Esteve-Núñez; Karina Boltes (Environmental Science and Ecotechnology)
50% of pharmaceuticals and 25% of herbicides used worldwide are chiral. Each enantiomer has a unique toxicity and biodegradation profile, affecting differently to organisms. Chirality plays a key role in the behavior of these emerging contaminants (ECs) in terms of their pharmacological or herbicidal activity, but this peculiarity is often overlooked in environmental research. The complexity of chiral ECs is underestimated, as the varying sensitivity of biological systems to enantiomers is rarely considered. Biofilters can promote the activity of specific microbial communities, facilitating the degradation of ECs, due to the greater interaction between water and microorganisms and their compact design. Here, we show that an electroactive biofilter can alter the chirality of drugs and herbicides in wastewater treatment, impacting their removal and toxicity. The electrochemical biofilter (BioeF) removed 80% of pharmaceuticals and 50–75% of herbicides, outperforming the conventional filter (ConF). BioeF also showed greater chiral alterations and lower ecotoxicity. This work provides the first evidence of a relationship between changes in contaminant chirality and detoxification capacity, enhanced by electroactive systems. The increased microbial activity observed in the BioeF suggests that bioelectrochemical systems offer a valuable advance for ECs removal and ecotoxicity reduction, addressing the environmental challenge posed by ECs.